The dilemma of rape victims in Malaysia: could compensation award be a solution? - Nur Aisyah Mohamed Ibrahim,; Mohamad Azhan Yahya,; Ahmad Azam Mohd Shariff,; Mohd Izzat Amsyar Mohd Arif,; Mohd Sabree Nasri, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The crime of rape is very much rampant in the society. It is a cruel form of sexual offence which leads to injuries to the party against whom it was committed coercively. The legal provisions to punish rape offenders are undoubtedly in existence under the Malaysian criminal law. However, these legal provisions are deemed inadequate in protecting the rights of the rape victims who suffered injuries as a result of such horrendous ordeal. This includes the absence of adequate provision which provides monetary compensation for rape victims. This paper aims at analyzing existing legal provisions under Malaysian criminal law. It then identifies the actual legal problem in the form of inadequate legal protection towards injurious rape victims. The paper simultaneously analyzes Syariah criminal principles on rape and diyyah (compensation or blood money in Islamic law). It consequently recommends solutions on how Malaysian criminal law can be amended to implement diyyah as monetary compensation for future rape victims. The paper adopts a doctrinal approach in its legal analysis. All data collected from library research as well as semi structured interview are analyzed qualitatively and critically. The paper additionally adopts referential method in comparing between the existing Malaysian criminal law and the syariah criminal principles on rape and diyyah. It also uses referential method in suggesting solutions in the form of legal amendments. The paper ultimately proposes the amendment of the relevant provision under the present Malaysian criminal law, paving the way for the implementation of diyyah as monetary compensation for future rape victims